2020
DOI: 10.1097/pcc.0000000000002136
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Electroencephalography in Pediatric Severe Traumatic Brain Injury

Abstract: Objectives: Electroencephalography is used in neurocritical care for detection of seizures and assessment of cortical function. Due to limited resolution from scalp electroencephalography, important abnormalities may not be readily detectable. We aimed to identify whether intracranial electroencephalography allows for improved methods of monitoring cortical function in children with severe traumatic brain injury. Design: This is a retrospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…9,10 Reductions in ADR have been associated with delayed cerebral ischemia in adult patients with aneurysmal subarachnoid hemorrhage 11 and cerebral perfusion pressure in pediatric TBI patients. 12 Here, we identified that PbtO 2 values < 10 mm Hg are associated with reduced ADR (Fig. 1).…”
Section: Discussionmentioning
confidence: 66%
“…9,10 Reductions in ADR have been associated with delayed cerebral ischemia in adult patients with aneurysmal subarachnoid hemorrhage 11 and cerebral perfusion pressure in pediatric TBI patients. 12 Here, we identified that PbtO 2 values < 10 mm Hg are associated with reduced ADR (Fig. 1).…”
Section: Discussionmentioning
confidence: 66%
“…This can manifest as a color dense spectral array (CDSA) or rhythmic spectrogram, making detection of pathologic patterns such as seizures and ischemia easier to recognize for bedside clinicians. In the previously described study of pediatric TBI patients undergoing iEEG, both surface and intracortical alphadelta ratios, a qEEG measure, were associated with CPP (58).…”
Section: Electroencephalographymentioning
confidence: 90%
“…Intracortical EEG (iEEG) has been increasingly utilized in adult neurocritical care (56) and is associated with improved signal-noise ratio, detection of seizures not captured on cEEG, clarification of equivalent cEEG patterns and detection of cortical spreading depolarizations (57). One pediatric TBI study utilized iEEG showing that 3/11 patients had epileptiform abnormalities not captured on scalp EEG (58). Quantitative EEG (qEEG) utilizes mathematical algorithms to compress raw cEEG into graphical data.…”
Section: Electroencephalographymentioning
confidence: 99%
“…CEEG can detect changes in EEG over time, thereby enabling the early initiation of treatment, and can evaluate response to treatment, if administered, over time. 16,21,[74][75][76][77][78][79] Considering the high-resolution time of CEEG, 30-33, 46, 80-83 this method offers a unique possibility to demonstrate that the brain undergoes continuous and dynamic functional changes during NDE and SCE remembering.…”
Section: Ceeg For Nde and Scementioning
confidence: 99%
“…CEEG is a rapidly evolving technology, and this statement addresses only current consensus-based recommendations for CEEG. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Hence, as the brain undergoes continuous and dynamic changes, CEEG should be an important method for real-time monitoring of the brain's functional changes during remembering NDE and SCE.…”
Section: Introductionmentioning
confidence: 99%